Nonlinear backstepping control design of half-car active suspension systems. (23rd February 2004) - Lin, J.-S.; Huang, C.-J.
This paper develops a novel nonlinear backstepping design for the control of half-car active suspension systems to improve the inherent tradeoff between ride quality and suspension travel. Since ride quality depends on a combination of vertical displacement (heave) and angular displacement (pitch) of a vehicle body, an active suspension controller must be able to minimise heave and pitch movements in order to guarantee ride comfort of passengers. Suspension travel means the space variation between body and tire. To avoid damaging vehicle components and generating more passenger discomfort, the controller must be capable of preventing the suspension from hitting it travel limits. Our design with an additional nonlinear filter shows potentials to achieve these conflicting control objectives. The novelty is in the use of the nonlinear filter whose effective bandwidths depend on the magnitudes of linear combination of the front and rear suspension travels. This intentional introduction of nonlinearity, which is conveniently accommodated by backstepping, results in a design that is fundamentally different from previous active suspension designs. As the suspension travel changes, the nonlinear controller smoothly shifts its focus between the conflicting objectives of ride comfort and rattlespace utilisation. The suspension is set to be soft when suspension travel is small, and it is adjusted to become stiff as it approaches the travel limits. Therefore, this nonlinear design allows the closed-loop system to behave differently in different operating regions, thereby eliminating the dilemma of whether to use a soft or stiff suspension setting. As a result, the improvement of tradeoff between ride quality and suspension travel is demonstrated through comparative simulations.